ZAKAT FUND DISTRIBUTION STRATEGY IN BAZNAS OF ROKAN HILIR DISTRICT - Nanda, Sayang Prima; Napitupulu, Rodame Monitorir; Hutagalung, Muhammad Wandisyah R. (Program Studi Manajemen Zakat dan Wakaf, 2023)
Zakat has an important role in the Islamic economic system. Meanwhile, if it is seen that the potential for zakat in Rokan Hilir Regency is quite large, this potential is obtained from professional zakat and wealth zakat. This research is descriptive qualitative, data analysis is carried out simultaneously with data collection. The analysis process is inductive in nature, namely collecting special information into a single unit by collecting data, compiling and classifying it and analyzing the implementation of the zakat fund distribution carried out by BAZNAS of Rokan Hilir Regency. The results of this study indicate that the BAZNAS of Rokan Hilir Regency in distributing zakat funds has already 5 programs aimed at mustahik namely: Rohil Cerdas, Rohil Makmur, Rohil Peduli, Rohil Sehat and Rohil Taqwa.